An academic visit by San Pedro College's School of Allied Health Science Delegation / Zakiah Mohd Noordin and Associate Prof. Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy at UiTM was honoured to host a delegation comprising 13 esteemed educators and administrators from San Pedro College's School of Allied Health Sciences (SAHS) on July 25th, 2023. Led by Prof. Fatima May R. Tesoro, Dean of SAHS, the delegates' visit aimed to forge new paths of international collaboration in various areas including academic, research, clinical activities and health technology. The visit commenced with a welcoming session by Dr. Norkasihan Ibrahim, Deputy Dean of Industry, Community, and Alumni Network (ICAN). This session provided an avenue for sharing UiTM's academic operations, innovations, and research ventures, laying the foundation for a comprehensive exchange of ideas and experiences. Engaging discussions took place between representatives from both institutions, exploring potential collaborations such as student exchange programs in digital health training and interdisciplinary research projects. These collaborative efforts hold the promise of transcending geographical boundaries and advancing the realm of healthcare education.